Assessing physico-chemical parameters of drinking water of different districts of Nepal - Basnet, Nabin (Damak Campus Journal, 2025)
Researchers assessed the quality of drinking water from several districts in Nepal by examining both physical and chemical properties. The physical parameters included pH, conductivity, total dissolved solids (TDS), colour, odour, and turbidity, while the chemical parameters covered hardness, ammonia, and iron. Together, these factors provided a comprehensive understanding of the region’s water quality. The findings revealed an average pH of 6.65, a conductivity of 442.9 µS/cm, and a TDS of 278.3 mg/L. Hardness averaged 224.8 mg/L, ammonia 0.312 mg/L, and iron 0.39 mg/L. Turbidity was also recorded at 0.312 mg/L. The samples were clear, odourless, and free from haze. All of the measured values fell within the limits set by the Nepal Drinking Water Quality Standards (NDWQS), indicating that the drinking water in the study areas is safe and suitable for consumption.